Isolation, Diversity, and Antimicrobial and Immunomodulatory Activities of Endophytic Actinobacteria From Tea Cultivars Zijuan and Yunkang-10 (Camellia sinensis var. assamica) - Wei, Wei; Zhou, Yu; Chen, Fanjie; Yan, Xiaomei; Lai, Yongmin; Wei, Chaoling; Chen, Xiaoyun; Xu, Junfeng; Wang, Xu (Frontiers in Microbiology, 2018)
Endophytic actinobacteria exist widely in plant tissues and are considered as a potential bioresource library of natural products. Tea plants play important roles in human health and in the lifestyles of Asians, especially the Chinese. However, little is known about the endophytic actinobacteria of tea plants. In this study, 16 actinobacteria of 7 different genera and 28 actinobacteria of 8 genera were isolated and analyzed by 16S rRNA gene sequencing from tea cultivars of Zijuan and Yunkang-10 (Camellia sinensis var. assamica), respectively. The diversity of actinobacteria species from Zijuan were higher in July than December (6 vs. 3 genera), but the diversity of species from Yunkang-10 were higher in December than July (7 vs. 3 genera). No actinobacteria isolates were obtained from any tea cultivar in September. Ten isolates from Yunkang-10 exhibited antimicrobial activity against at least one human pathogenic microorganism (Staphylococcus epidermidis, Shigella flexneri, and Escherichia coli), but none of the isolates from Zijuan exhibited antimicrobial activities. Fourteen strains were further exammined the genes of polyketide synthetase (PKS)-I and PKS-II and nonribosomal peptide synthetase (NRPS). Brevibacterium sp. YXT131 from Yunkang-10 showed strong inhibitory activity against S. epidermidis, Sh. flexneri, and E. coli, and PKS-I and PKS-II and NRPS genes were obtained from the strain. In in vitro assays, extracts from 14 actinobacteria that were tested for antibiotic biosynthetic genes showed no inhibition of concanavalin A (ConA)-induced murine splenocyte proliferation. In in vivo assays, the crude extract of YXT131 modulated the immune response by decreasing the proinflammatory cytokines interleukin (IL)-12/IL-23 p40 and tumor necrosis factor (TNF)-a in the serum of mice. These results confirm that endophytic actinobacteria from tea plants might be an undeveloped bioresource library for active compounds.